Pengaruh latihan strokes dan drilling dropshot terhadap peningkatan dropshot dalam permainan bulutangkis pada atlet pb warna agung perkasa mataram - Muhammad Fahmul Qur’ani; Andi Gilang Permadi; Kurnia Taufik (Jurnal Pengetahuan dan Pendidikan, 2024)
This research is motivated by observations made by researchers at the "PORPROV 2023" championship, regarding the increase in Dropshot by PB Warna Agung Perkasa Mataram athletes who participated in the PROPROV championship which still often makes mistakes and lacks implementation. This study aims to determine the impact of applying the Strokes and Drilling Dropshot training methods to increasing Dropshot in badminton games. The method used in this study is an experimental method with a research design of two groups pretest and posttest design with 10 treatments. In this study the authors took a sample of 10 people. Based on processing and analysis of increased data from the initial test results obtained a value of 233 and the final test obtained a value of 297, the difference between the initial test and the final test was 64. While the hypothesis test with a similar sample t test obtained the results of the exercise strokes t-count 6.650> t-table 2.132 while the results of drilling dropshot t count 3.553> t-table 2.132. Thus Ho is rejected and Ha is accepted. So the researchers drew 2 conclusions, namely: (1) There is an effect of Strokes Exercise on increasing dropshot in PB Warna Agung Perkasa Mataram Athletes in 2023. (2) The strokes training method has more impact on increasing dropshot than the drilling dropshot training method with a posttest mean difference of 3.097. The research instrument used is to test and measure the increase in badminton dropshot that has been determined by PB PBSI (2006: 36).